Vliv cyklofosamidu na metabolismus erytrocytů - Prokes, J; Sromová, S; Vulterin, K; Proksová, M; Graham, G (Veterinarni medicina, 1975)
Cyclophosphamide was applied i.p. in the dose of 100 mg kg-1 to rats. After one, two, three, and seven days the animals were killed and in the collected heparinized blood the incorporation of o-phosphate 32P in erythrocytes was determined in vitro at 37 degrees C and in 35 minutes. Decreased incorporation in animals with Cyclophosphamide indicated, compared with the control, disturbed metabolism of phosphate. The method can be applied as a criterion of secondary toxic effects in the treatment of cancerostatics of alkylation type.
Keywords: Phosphorus Radioisotopes; Cyclophosphamide; Erythrocytes; fosfáty; Chemical Phenomena; erytrocyty; zvířata; krysa rodu Rattus; chemické jevy; ženské pohlaví; cyklofosfamid; Female; chemie; Animals; Rats; Chemistry; radioizotopy fosforu; Phosphates